Knowledge, attitude and practice regarding toilet training among mothers of toddler at Kalika Municipality, Chitwan - Sharma, Pabitra; Gurung, Ganga; Regmi, Shanti (Journal of Chitwan Medical College, 2018)
Abstract available on the PDF.